Recontextualization of improvement-oriented policies in Portugal: The case of the pilot project for pedagogical innovation (2016-2019). (2021) - Carvalho, Luís Miguel; Costa, Estela; Almeida, Marta
Highlights: PPIP as an example of composite modes of governing education in Portugal School-level recontextualization involves the reconfiguration of power relations Cooperation bureaucracy-profession partly achieved by the validation of what works European expert networks effect on PPIP policy texts and contexts of practice Abstract: The paper focus is the political processes of recontextualization, in Portuguese schools, of a policy pilot to combat retention and dropout, in basic/secondary education, through improvement-oriented school projects. Based on data from a mixed method study, carried out in six school clusters, the results show the pilot project as an example of the State's use of composite modes of governing education, merging emergent soft governing discourses and coordination and control forms to alter the ways in which the actors adjust to the circumstances of their social practices, and the persistence of a centralized regime for the administration of education, institutional and historically rooted, seeking the social actors' compliance with the formal rules.